Unprecedented O:⇔:O compression and H↔H fragilization in Lewis solutions - Sun, Chang Qing (2020)
Charge injection in terms of lone pairs ‘:’, protons, and ions upon acid and base solvation mediates thehydrogen bonding network and properties of Lewis solutions, and is ubiquitously important in manysubject areas of Chemical Physics. This work features the recent progress and future trends in thisaspect with a focus on the solute–solvent interactions and hydrogen bond (O:H–O or HB) transitionfrom the vibration mode of ordinary water to the hydrating states. A combination of the O:H–O bondcooperativity notion, differential phonon spectrometrics, calorimetric detection, and quantum computa-tions clarified the solute capabilities of O:H–O bond transition in HX and YOH (X = Cl, Br, I and Y = Li,Na, K) solutions. The H+and the lone pair do not stay alone to move or shuttle freely between adjacentH2O molecules, but they are attached to a H2O molecule to form (H3O+and OH ) 4H2O tetrahedralmotifs, which transits an O:H–O bond into the H2H anti-HB point breaker in acidic solutions and intothe O:3:O super-HB compressor and polarizer in basic solutions, respectively. H2H disrupts the sol-vent network and surface stress, having the same effect of liquid heating on HB bond relaxation andthermal fluctuation on surface stress. The O:3:O compression lengthens and weakens the solute H–Obond, which heats up the solution during solvation. The H–O bonds due to H3O+contract by 3% anddue to OH shrink by 10%. The Y+and X ions perform in the same manner as they do in salt solutionsto form hydration shells through electrostatic polarization and hydrating H2O dipolar screen shielding.Focusing more on the O:H–O bond transition would be even more promising and revealing than on themanner and mobility of lone pair and proton transportation.